The evaluation of 06-methylguanine-DNA-methyltransferase (MGMT) gene methylation status among Hospital Universiti Sains Malaysia glioma patients - Murali, Revathy (2018)
Growing evidences demonstrate the understanding of the biomarkers and it significantly increased our current perception of gliomagenesis, prognostic evaluation, and treatment planning for the patients. For instance, identification of the promoter methylation status of O6-methylguanine-DNA-methyltransferase (MGMT) gene encodes MGMT, a protein with DNA repair activity may improve the efficacy of current standard care in glioma as the methylation status has been recently introduced to be a predictive biomarker for stratification of the treatment plan. To further understand the roles of MGMT, we aimed to evaluate the MGMT promoter methylation status of glioma patients in Hospital USM. In this study, 41 samples of paraffinembedded glioma tissue (FFPE) were obtained based on their grading from Grade II (n = 11), III (n = 10) and IV (n = 20). Subsequently, DNA extraction and methylation status was validated by methylation-specific PCR (MSP) method using two pairs of primers specifically targeting the unmethylated (UM) and methylated (M) regions of the MGMT gene, respectively. MSP results identified high intratumoral heterogeneity of the samples in all grades of the tumours. In Grade II glioma, 9.1% were M and 90.9% were combination of UM and M. Moreover, Grade III glioma indicated 50% M and combination of UM and M, respectively. Besides, Grade IV glioma exhibited 15% were UM, 30% were M and 55% were both UM and M. Nevertheless, analysis using Fisher’s exact test found no statistical association of the MGMT methylation status with any of the tested clinicopathological parameters such as tumour grade, age, gender, and race of the patients (p > 0.05). In conclusion, this study found frequent MGMT methylation, regardless of the tumour grade, age, gender and race of the glioma patients at Hospital USM. Moreover, the occurrence of MGMT combination status in all grades of gliomas suggested intratumoral heterogeneity of the tumour. Besides imparting intratumoral diversity, it may also indicate possible challenges in defining personalized treatment based on the epigenetic status of MGMT.